Methodological instructions to perform practical works on discipline "Code of Professional Ethics for Accountants and Auditors" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
Today, one of the critical issues is professional ethics, which is an integral part of the development of society. Any profession and specialty requires specific ethical standards of behavior. Every person engaged in one activity, to one degree or another, is interested in society's trust in the results of their activities and the high quality of the services provided, and accordingly, a high assessment of the results of their activities by society. - Form a holistic system of knowledge among students regarding professional values and requirements of accountants' professional ethics and practical application in the interests of society and the profession.
Keywords: methodological instructions; economic activity; finance; audit; ethics of personality; ethics of character; business; conflicts